Modulation of Efficient Diiodo-BODIPY in vitro Phototoxicity to Cancer Cells by Carbon Nano-Onions - Bartelmess, Juergen; Milcovich, Gesmi; Maffeis, Viviana; d'Amora, Marta; Bertozzi, Sine Mandrup; Giordani, Silvia (Frontiers in Chemistry, 2020)
Photodynamic therapy (PDT) is currently one of the most promising approaches for targeted cancer treatment. It is based on responses of vital physiological signals, namely reactive oxygen species (ROS), which are associated with diseased condition development, such as tumors. This study presents the synthesis, incorporation, and application of a diiodo-BODIPY based photosensitizer, based on a non-covalent functionalization of carbon nano-onions (CNOs). In vitro assays demonstrate that HeLa cells internalize the diiodo-BODIPY molecules, and their CNOs nanohybrids. Upon cell internalization and light exposure, the pyrene-diiodo-BODIPY molecules induce an increase of the ROS level of HeLa cells, resulting in remarkable photo-mediated cytotoxicity and apoptosis. Conversely, when HeLa cells internalize the diiodo-BODIPY/CNOs nanohybrids, no significant cytotoxicity or ROS basal level increase can be detected. These results define a first step towards the understanding of carbon nanomaterials that function as molecular shuttles for photodynamic therapeutics, boosting the modulation of the photosensitizer.